Self- and Co-Worker Perceptions of Ethics and Their Relationships to Leadership and Salary - Morgan, Ronald B. (Academy of Management Journal, 1993)
This research examined perceptions of ethics on the premise that such perceptions have important implications for ethical behavior in organizations. Various raters assessed managers' ethics; subordinates and peers provided the least favorable assessments, which were directly related to perceptions of leadership but inversely related (for ratings by subordinates) to salary data. Implications for fostering ethical behavior in organizations are discussed.